2012
DOI: 10.1179/1743284711y.0000000054
|View full text |Cite
|
Sign up to set email alerts
|

Netted structure of grain boundary phases and its influence on electrical conductivity of Cu–Ni–Si system alloys

Abstract: Cu-Ni-Si alloys with four different Cu contents were fabricated by means of smelting. Subsequently, isothermal aging and hot rolling followed by aging treatment were carried out. The microstructure and phase composition were characterised by optical microscope, transmission electron microscope and X-ray diffractometer. Electrical conductivity was measured by using an eddy current based technique. The results show that the electrical conductivities of as cast Cu-Ni-Si alloys decrease obviously with a decline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The conductivity of T2 pure Cu matrix is 98.7% IACS and the Cu–diamond/Cu–diamond-Cu2NiAlAgZn bi-layer leads to a significant decrease in conductivity. The electrical conductivity of copper and copper matrix composites can be expressed by the following equation 39 : where ρ 0 is the matrix resistivity; ρ pho , ρ pre , ρ sol , ρ def and ρ int are the contributions to the resistivity from phonon scattering, precipitation scattering, solid solution scattering, defect scattering and interfacial scattering, respectively; σ and ρ are the electrical conductivity and resistance, respectively. It follows that a large number of second phases and interfaces are present in MA-II, which leads to a significant increase in electrical resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity of T2 pure Cu matrix is 98.7% IACS and the Cu–diamond/Cu–diamond-Cu2NiAlAgZn bi-layer leads to a significant decrease in conductivity. The electrical conductivity of copper and copper matrix composites can be expressed by the following equation 39 : where ρ 0 is the matrix resistivity; ρ pho , ρ pre , ρ sol , ρ def and ρ int are the contributions to the resistivity from phonon scattering, precipitation scattering, solid solution scattering, defect scattering and interfacial scattering, respectively; σ and ρ are the electrical conductivity and resistance, respectively. It follows that a large number of second phases and interfaces are present in MA-II, which leads to a significant increase in electrical resistance.…”
Section: Resultsmentioning
confidence: 99%
“…With increasing number of forging passes, the electrical conductivity first increased and then decreased, while the hardness increased continuously until it slightly decreased when the number of forging passes exceeded 18. According to the electron mechanism, electrical conductivity is affected by phonon scattering, dislocations, solution atoms, precipitates, grain boundaries, interfaces, and impurities [27,28]. However, for precipitation-strengthened Cu-Ni-Si alloys, the most important factors are the solution atoms and precipitates [29].…”
Section: Variation In Electrical Conductivity and Hardness During Multiple Forgingmentioning
confidence: 99%
“…However, for precipitation-strengthened Cu-Ni-Si alloys, the most important factors are the solution atoms and precipitates [29]. Considering the microstructural evolution of the as-cast Cu-Ni-Si alloy after multiple forging for different numbers of passes, it can be easily confirmed that the increase in electrical conductivity is due to the destruction of the reticular Ni 31 Si 12 phase, which is located on the grain boundaries and has poor conductivity; hence, it has a very negative effect on the electrical conductivity [20]. The decrease in electrical conductivity is the result of the dissolution of Ni 2 Si precipitates because the atoms degrade the electrical conductivity considerably more in solid solution than as precipitates [30].…”
Section: Variation In Electrical Conductivity and Hardness During Multiple Forgingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a case is true to Cu–Ni–Si alloys with low Ni and Si addition, in which δ -Ni 2 Si precipitates have significant influence on the strength as well as the directional movement of electrons. However, for high Ni and Si addition, besides δ -Ni 2 Si precipitates in the copper matrix, the influence of Ni 3 Si phases formed at the grain boundaries on tensile strength and electrical conductivity must also be taken into consideration 11. Thus, it is very important to realise an excellent combination of strength and electrical conductivity by controlling effectively the amount, distribution as well as size of nickel silicides.…”
Section: Introductionmentioning
confidence: 99%